Continuing Medical Education Network, Identification of Technical, Organizational, and Human Barriers. - Bagayoko, Cheick Oumar; Naef, Jean Marc; Maiga, Habyata; Traoré, Abdel Kader; Geissbuhler, Antoine (Journal of Health Informatics in Africa, 2016)
Background and Purpose: The aim of this research is to find out if by putting in place a new platform accordingly to local conditions of the developing countries and by eliminating the technical obstacles could uncover other organizational and human. Methods: This study is being done for the RAFT project and involves users of the distance learning systems. It focusses on two distinct series of questions. Results: The findings have clearly shown that the network can have a great and positive impact on the African healthcare system by creating an access to a continuous medical training and virtually networking medical centers that are otherwise geographically isolated and difficult to access. Conclusions: At the end of this study the human and organizational barriers often considered as technical issues by the users have been identified as the main reasons of the under-usage of the network. Further research would be needed to evaluate the new system and solve the issues discovered in this study